Digital Leadership in Accelerating Bureaucratic Transformation: Evidence from the Implementation of SRIKANDI and Electronic Signatures in an Indonesian Provincial Government - Iskandar; Hari Yeni; Tri Vena Desi Sutomo; Maslia (PT. LITERASI SAINS NUSANTARA, 2026)
The implementation of the Electronic-Based Government System (SPBE) has become a strategic priority for the Indonesian government to improve bureaucratic efficiency, transparency, accountability, and the quality of public services through digital transformation. However, the adoption of digital government applications remains uneven across regional institutions due to organizational resistance, limited digital competencies, and challenges in managing institutional change. This study aims to examine how digital leadership, regulatory intervention, and technical facilitation accelerate bureaucratic transformation through the implementation of the Integrated Dynamic Archival Information System (SRIKANDI) and Electronic Signatures (TTE) at the West Sulawesi Provincial Department of Cooperatives, SMEs, Industry, and Trade. A qualitative descriptive case study approach was employed using purposive sampling. Primary data were collected through semi-structured interviews, non-participant observations, and document analysis, while data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that successful implementation of SRIKANDI and TTE was driven by the synergy between strong digital leadership, mandatory regulatory enforcement, and continuous technical mentoring. These complementary factors reduced organizational resistance, improved employees' digital competencies, accelerated the transition from paper-based administration to integrated digital governance, and significantly enhanced administrative efficiency, transparency, and accountability. This study contributes to the digital government literature by demonstrating that sustainable bureaucratic transformation depends not only on technological readiness but also on the integration of leadership commitment, institutional support, and organizational learning. The findings provide practical recommendations for strengthening SPBE implementation across regional government institutions in Indonesia.